Validating a Collaborative Writing Competence Framework for EFL Instruction: A Confirmatory Factor Analysis Approach - Mujiono; Weganofa, Riza; Herawati, Siane; Lutviana, Rizky (VELES Voices of English Language Education Society, 2025)
Collaborative writing is widely recognized for its benefits in enhancing linguistic competence, critical thinking, and social interaction in EFL contexts. Despite numerous studies highlighting these advantages, a gap remains in how collaborative writing competence can be systematically assessed and practically applied in classroom settings. This study aims to empirically validate a Collaborative Writing Competence Framework (CWCF) comprising five key dimensions: communication, coordination, creativity, responsibility, and reflection. A quantitative research design involved 103 Indonesian undergraduate EFL students enrolled in an Essay Writing course. Data were collected using a Likert-scale questionnaire and analyzed through Confirmatory Factor Analysis (CFA). The model demonstrated a good fit (χ² = 86.528, df = 81, p = .317; CMIN/DF = 1.068; RMSEA = 0.026; CFI = 0.992), with acceptable reliability (Cronbach’s α = 0.719–0.807) and convergent validity (AVE = 0.501–0.673). Creativity emerged as the most influential factor in collaborative writing competence. The validated CWCF offers actionable insights for EFL instruction: structured peer discussions, guided brainstorming, and task delegation can enhance collaboration, while integrating self- and peer-assessment fosters responsibility and reflection. Digital platforms such as Google Docs may also support real-time coordination and feedback. The CWCF thus serves as both an assessment instrument and pedagogical tool, paving the way for more effective collaborative writing practices in EFL classrooms.